Extradition law : reviewing grounds for refusal from the classic paradigm to mutual recognition and beyond - Costa, Miguel João (Human Rights and Humanitarian Law E-Books Online, Collection 2019, ISBN: 9789004390775., 2020)
"In Extradition Law, Miguel João Costa offers not only an exhaustive review of this legal area and of transnational criminal law more generally, but also innovative solutions for their reform. The book critically analyses numerous themes - from international cooperation in criminal matters to substantive criminal law and procedure, from human rights to nationality and refugee law, from public to private international law - at the national, European and global levels. Moreover, while it is a fundamentally normative study, it does not disregard the political and diplomatic dimensions of extradition either. The result is a new model based on mutual respect, enabling States to increase cooporation whilst preserving the integrity of their own criminal justice values and enhancing the respect for human rights."